Perancangan Sistem Informasi Penyewaan Karangan Bunga pada Delima Florist Menggunakan Metode Prototype - Khairul Fajri Ilahi; Boy Sandy Dwi Nugraha H.; Herlina H. (Universitas Methodist Indonesia, 2026)
Delima Florist is a company engaged in flower board rental services, currently focusing on providing flower board rentals in Padang. At present, Delima Florist is able to serve flower board orders from customers both within Padang and from outside the city. Currently, the flower board ordering process at Delima Florist is still carried out conventionally by using a communication application, after which the orders are manually recorded in an order ledger. This has led to several serious issues, such as customer orders frequently not being properly recorded, resulting in the flower boards not being produced by the Florists. Another issue is the frequent loss of flower boards after the rental period, caused by customers failing to return them to Delima Florist. The purpose of developing this flower board rental information system is to automate the processes of ordering, production recording, and flower board returns. This system is expected to make it easier for staff to monitor orders, deliveries, and returns of flower boards. The flower board rental information system will be developed using the Prototype method, while the process flow and system design will utilize Unified Modeling Language (UML).